The Influence of Product Quality and Price on Purchasing Decisions at Mitraindo South Tangerang Online Shop - Mada Faisal Akbar (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
This study aims to determine the effect of product quality and price on purchasing decisions at Mitraindo South Tangerang Online Shop. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study product quality significantly influence purchasing decisions by 40.3, the hypothesis test obtained tcount> ttable or (7.974> 1.986). Price significantly influences the purchase decision of 38.0%, the hypothesis test is obtained tcount> ttable or (7.594> 1.986). Product quality and price simultaneously have a significant effect on purchasing decisions of 49.0%, the hypothesis test is obtained Fcount> Ftable or (44,626> 2,700)